Naturalistic Parent Teaching in the Home Environment During Early Childhood - Della Porta, Sandra L.; Sukmantari, Putri; Howe, Nina; Farhat, Fadwa; Ross, Hildy S. (Frontiers in Psychology, 2022)
Children’s sociocultural experiences in their day-to-day lives markedly play a key role in learning about the world. This study investigated parent–child teaching during early childhood as it naturally occurs in the home setting. Thirty-nine families’ naturalistic interactions in the home setting were observed; 1033 teaching sequences were identified based on detailed transcriptions of verbal and non-verbal behavior. Within these sequences, three domains of learning (knowledge, skills, and dispositions) and subtopics were identified and analyzed in relation to gender, child birth order, context, teaching strategies, and learner response. Findings show knowledge, skills, and dispositions were taught equally, marked by the most prominent subtopics taught within each domain, including cognitive (skill), game rule (knowledge), and social rule (disposition). Further, mothers and fathers were found to teach their children equally, however, fathers taught knowledge more than mothers, whereas mothers taught dispositions more than fathers. Differences between domains of learning and subtopics also existed between mother’s and father’s teaching based on child birth order and gender. This study also assessed the contrast between teaching knowledge, skills, and dispositions by context, parent teaching strategies, and child learner response. Results support the notion that family interactions in the home setting set a stage for children’s rich informal learning experiences. Vygotskian sociocultural conceptions underpin this research and findings are discussed using this central theoretical lens.